Metabolic Pathway of Osilodrostat in Equine Urine Established through High-resolution Mass Spectrometric Characterization for Doping Control - Ishii, Hideaki; Shigematsu, Ryo; Takemoto, Shunsuke; Ishikawa, Yuhiro; Mizobe, Fumiaki; Nomura, Motoi; Arima, Daisuke; Kunii, Hirokazu; Yuasa, Reiko; Yamanaka, Takashi; Tanabe, Sohei; Nagata, Shun-ichi; et al. (Current Drug Metabolism, 2024)
ObjectiveOsilodrostat, used to treat Cushing's disease, exhibits an anabolic effect, leading to its classification as a prohibited substance in horseracing and equestrian sports. This study reports the characterization of osilodrostat metabolites in horse urine and elucidates its metabolic pathways for the first time for doping control purposes.MethodsOsilodrostat was administered nasoesophageally to four thoroughbreds (one gelding and three mares) at a dose of 50 mg each. Potential metabolites were extensively screened via our developed generic approach employing differential analysis to identify metabolites. Specifically, high-resolution mass spectral data were compared between pre- and post-administration samples on the basis of criteria of fold-changes of peak areas and their P values. Potential metabolite candidates were further identified through mass spectral interpretations using product ion scan data.ResultsA total of 37 metabolites were identified after comprehensive analysis. Osilodrostat was predominantly metabolized into a mono-hydroxylated form M1c ( 40%) alongside osilodrostat glucuronide M2 ( 17%). Given their longest detection time (2 weeks after administration) and the identification of several conjugates of osilodrostat and M1c, including a novel conjugate of riburonic acid, we recommend monitoring both osilodrostat and M1c after hydrolysis during the screening stage. However, only osilodrostat can be used for confirmation because of the availability of a reference material.ConclusionIt is advisable to screen for both osilodrostat and its mono-hydroxylated metabolite M1c to effectively monitor horse urine for the potential misuse or abuse of osilodrostat. For suspicious samples, confirmation of osilodrostat using its reference material is required.
Keywords: anabolic